NILAI-NILAI PENDIDIKAN KARAKTER DALAM KITAB TA’LIM MUTA’ALLIM DAN AYYUHAL WALAD KARYA SYEIKH BURHANUDDIN AL-ZARNUJI DAN IMAM GHAZALI - Uswatun Hasanah; Chalimatus Sa'dijah; Ach. Faisol (VICRATINA, 2019)
In todays modren era, education in Indonesia gradually loses its spiritual essence. This is because of advancing technology and every accessable informations to all olds and youngs without including the moral values. As a result the values of essence education are easily eliminated by the Indonesian people. The Book Ta'lim Muta'allim and Ayyuhal Walad by Al-zarnuji and Imam Ghazali, a classical book containing the values that have relevance to the nation's educational character applied in educational institutions in Indonesia. This type of research is a Research Library by using descriptive method and data analysis (content analysis). Values of the character education contained in Ta'lim Muta'allim include: Good Intentions, Speeches, Patience and Worship, Respect and Servant, Self-esteem, Self-Help, Absolute Idea, Hard Work, Tawakkal, Mutual Advise, Take Lesson, Wara'. While the values of character education contained in Ayyuhal Walad's book include: Obedience to God, Glorifying Time, Practicing Science, Muroja'ah Skills (Repeatings), Istifadah, Peace Behavior, Sincerity and Generosity, Honorable Idea, Honorable , Tolerance, Trust, Good and Sociable, Tawaddhu'for teacher.